2016
DOI: 10.1016/j.celrep.2016.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Ezh2 Controls an Early Hematopoietic Program and Growth and Survival Signaling in Early T Cell Precursor Acute Lymphoblastic Leukemia

Abstract: SUMMARYEarly T cell precursor acute lymphoblastic leukemia (ETP-ALL) is an aggressive subtype of ALL distinguished by stem-cell-associated and myeloid transcriptional programs. Inactivating alterations of Polycomb repressive complex 2 components are frequent in human ETP-ALL, but their functional role is largely undefined. We have studied the involvement of Ezh2 in a murine model of NRASQ61K-driven leukemia that recapitulates phenotypic and transcriptional features of ETP-ALL. Homozygous inactivation of Ezh2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 73 publications
(105 reference statements)
4
79
0
1
Order By: Relevance
“…These inactivating mutations of EZH2 predict a poorer overall outcome in CMML, MDS, and PMF (Grossmann et al 2011;Guglielmelli et al 2011). Conditional loss of Ezh2 in a hematopoietic system contributes to the pathogenesis of MDS and accelerates the onset of the early T-cell precursor ALL (ETP-ALL) induced by oncogenic NRAS Q61K (Score et al 2012;Muto et al 2013;Danis et al 2016). Besides EZH2 inactivating mutations, loss-of-function mutations of the PRC2 core components SUZ12 and EED have also been detected in T-ALL, all of which lead to lower levels of H3K27me3 (Ntziachristos et al 2012;Simon et al 2012).…”
Section: Polycomb Group (Pcg) Proteins In Normal and Malignant Hematomentioning
confidence: 99%
“…These inactivating mutations of EZH2 predict a poorer overall outcome in CMML, MDS, and PMF (Grossmann et al 2011;Guglielmelli et al 2011). Conditional loss of Ezh2 in a hematopoietic system contributes to the pathogenesis of MDS and accelerates the onset of the early T-cell precursor ALL (ETP-ALL) induced by oncogenic NRAS Q61K (Score et al 2012;Muto et al 2013;Danis et al 2016). Besides EZH2 inactivating mutations, loss-of-function mutations of the PRC2 core components SUZ12 and EED have also been detected in T-ALL, all of which lead to lower levels of H3K27me3 (Ntziachristos et al 2012;Simon et al 2012).…”
Section: Polycomb Group (Pcg) Proteins In Normal and Malignant Hematomentioning
confidence: 99%
“…A study modeling early T cell progenitor ALL in mice through the use of a mutant oncogenic form of the small GTPase NRAS (NRAS-Q61K) has shown that genetic inactivation of EZH2 or EED (another core subunit of the PRC2 complex) act cooperatively with mutant NRAS in leukemogenesis through enhancement of a stem-cell-related transcriptional program and increased phosphorylation and activation of the transcription factor STAT3 (ref. 65). …”
Section: Prc2 In Leukemia and Lymphomamentioning
confidence: 99%
“…In contrast, specific targeting of a tumor suppressor to restore normal function has been reported but remains challenging. However, loss of tumor suppressors, such as SOCS2 or PRC2, leads to hyperactivation of the JAK-STAT pathway which could be targeted instead [8,9]. …”
Section: Identification Of Key Driver Mutations In Hematopoietic Cancermentioning
confidence: 99%